Politik Hukum Pemberian Kompetensi Absolut Peradilan Tata Usaha Negara dalam Pengujian Penyalahgunaan Wewenang - Fauzi Syam; Sukamto Satoto; Helmi Helmi (Undang: Jurnal Hukum, 2023)
There have been differing views on the administrative court’s absolute competence in reviewing abuse of authority cases under Law No. 30/2014 on Government Administration (Government Administration Law). This article seeks to uncover the legal politics and principles underlying the grant of absolute competence to the administrative court in reviewing abuse of authority cases. The uncovered legal politics and principles will then be used to analyze the regulation of objects, subjects, and the limits of the administrative court’s authority under Supreme Court Regulation No. 4/2015. The study’s findings concluded that the underlying idea behind the grant of authority to the administrative court in reviewing abuse of authority cases is to ensure legal certainty and protection for government officials in the exercise of their duties and authorities as stated under Art. 17 to Art. 21 of the Government Administration Law. The legislators shifted their anti-corruption law approach from a criminal-based approach to an administrative-based approach that prioritizes the recovery of state funds and enforcing administrative sanctions. Conceptually, this new model of anti-corruption law enforcement is founded on three principles: the presumption of legality, the presumption of administrative violation, and the ultimum remedium principle. Finally, Supreme Court Regulation No. 4/2015’s regulation of objects, subjects, and limits on administrative court authority contradicts the legal-philosophical idea underlying Art. 17 to Art. 21 of the Government Administration Law. Abtrak Sampai saat ini, masih beragam pandangan mengenai eksistensi kompetensi absolut peradilan tata usaha negara (peratun) dalam pengujian penyalahgunaan wewenang dalam UU No. 30/2014 tentang Administrasi Pemerintahan (UU AP). Artikel ini bertujuan untuk menemukan gagasan filosofis politik hukum dan prinsip-prinsip dalam pemberian kompetensi absolut kepada peratun dalam pengujian penyalahgunaan wewenang dalam UU AP sekaligus sebagai pisau untuk menganalisis pengaturan objek, subjek, dan pembatasan kewenangan PTUN dalam Perma No. 4/2015. Hasil kajian menyimpulkan, pertama, gagasan filosofis politik hukum pemberian kompetensi absolut kepada PTUN dalam pengujian penyalahgunaan wewenang bertujuan untuk memberikan kepastian hukum dan perlindungan hukum kepada pejabat pemerintahan dalam melaksanakan tugas dan wewenangnya sebagaimana diatur dalam Pasal 17 s.d. Pasal 21 UU AP. Pembentuk UU mengubah cara pandang hukum pemberantasan korupsi yang sebelumnya mengutamakan ‘pendekatan penindakan pidana’ menjadi ‘pendekatan administratif’; dari pendekatan yang ‘mengutamakan penghukuman pidana penjara’ menjadi ‘mengutamakan pengembalian uang negara’ dan ‘penegakan sanksi administratif’. Secara konseptual, model baru penegakan hukum tersebut memiliki basis teoretis yaitu asas praduga rechtmatige, asas praduga pelanggaran administratif, dan asas ultimum remedium. Kedua, pengaturan objek, subjek, dan pembatasan kewenangan PTUN dalam Perma No. 4/2015 tidak sesuai dengan gagasan filosofis politik hukum dan bertentangan dengan prinsip-prinsip dalam Pasal 17 s.d. Pasal 21 UU AP.